Antonymy in Surat Al-Baqara - Hassan, Aalaa Yaseen (Journal of Humanities & Social Sciences, 2020)
Antonymy is generally defined as relations of opposition or contrast in meaning. In Arabic, antonyms are somehow used differently from English. It is classified into three divisions in Arabic and into two divisions in English. This study aims at applying the Arabic classification of antonymy on Sura Al-Baqara and determining types of opposite words; besides, it adds a new classification of antonymy in Arabic which is known as implied antonymy. Both qualitative and quantitative approaches are used to collect and analyze the data. Quantitative research deals with numbers and statistics, while qualitative research deals with words and meanings in this research. The results of the analysis data show that the positive antonymy is the most popular types, and implied antonymy is higher than the negative one. This study contributes to understand types of antonymy and helps the students who are interested in to distinguish them easily.